Morphogenesis and bone integration of the mouse mandibular third molar - Chlastakova, Ivana; Lungova, Vlasta; Wells, Kirsty; Tucker, Abigail S; Radlanski, Ralf J; Misek, Ivan; Matalova, Eva (European journal of oral sciences, 2011)
The mouse third molar (M3) develops postnatally and is thus a unique model for studying the integration of a non-mineralized tooth with mineralized bone. This study assessed the morphogenesis of the mouse M3, related to the alveolar bone, comparing M3 development with that of the first molar (M1), the most common model in odontogenesis. The mandibular M3 was evaluated from initiation to eruption by morphology and by assessing patterns of proliferation, apoptosis, osteoclast distribution, and gene expression. Three-dimensional reconstruction and explant cultures were also used. Initiation of M3 occurred perinatally, as an extension of the second molar (M2) which grew into a region of soft mesenchymal tissue above the M2, still far away from the alveolar bone. The bone-free M3 bud gradually became encapsulated by bone at the cap stage at postnatal day 3. Osteoclasts were first visible at postnatal day 4 when the M3 came into close contact with the bone. The number of osteoclasts increased from postnatal day 8 to postnatal day 12 to form a space for the growing tooth. The M3 had erupted by postnatal day 26. The M3, although smaller than the M1, passed through the same developmental stages over a similar time span but showed differences in initiation and in the timing of bone encapsulation.
Keywords: proliferační antigen buněčného jádra; fibroblastový růstový faktor 4; orgán skloviny; apoptóza; zubní zárodek; Fibroblast Growth Factor 4; Molar; Tooth Germ; Hedgehog Proteins; Osteoblasts; počítačové zpracování obrazu; prořezávání zubů; proteiny hedgehog; Enamel Organ; Tissue Culture Techniques; odontogeneze; Mice; Cell Proliferation; molár třetí; Morphogenesis; moláry; kyselá fosfatasa; Osteogenesis; Tooth Root; Molar, Third; Proliferating Cell Nuclear Antigen; Tooth Eruption; processus alveolaris; resorpce kosti; Bone Resorption; Mandible; osteoblasty; osteogeneze; Isoenzymes; zvířata; techniky tkáňových kultur; biologické markery; osteoklasty; izoenzymy; zobrazování trojrozměrné; Tooth Calcification; hybridizace in situ; Alveolar Process; myši; Acid Phosphatase; proliferace buněk; mandibula; morfogeneze; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Apoptosis; zubní kořen; Tartrate-Resistant Acid Phosphatase; Biomarkers; Odontogenesis; In Situ Hybridization; kyselá fosfatasa rezistentní k tartarátu; Osteoclasts; kalcifikace zubů; Animals